Design of Laboratory Scale Oil Distillation Machine - Satria, Dhimas; Rosyadi, Imron; Irman, Ade; Lusiani, Rina; Haryadi, Haryadi; Siregar, Abdul Rahman (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2016)
In Indonesia there are 4,000 old oil wells are not exploited again by Pertamina becauseit is not economical, some old wells exploited and processed in the traditional way.Their traditional oil processing has not significantly give a role to the income of localcommunities, as the mining process that is not managed by modern technologyresulting in a weak bargaining position. This study aims to participate in the welfare ofthe community in areas rich in oil resources and also support the energy security bydeveloping technologies distillationof crude oil into diesel by exploiting oil wellsparents who are not exploited again by Pertamina that will improve the bargainingposition (bargaining power), increase revenue, reduce unemployment and poverty andhas created a system of social safety nets and insurance against society.The methodused is the method of Pahl and Beitz, which consists of the Planning and TaskClarification, Conceptual Design, Embodiment Design, and Detail Design.The results ofthe research are the best variant for the design of machines fractional distillation ofpetroleum laboratory scale variant 1 (Boiler cylinder - 0.5 inch Pipe - Tubes distillationcylinder - gas stove), by reason of the appropriate size pipe diameter and more securethan the variance other variants. While the dimensions obtained from the draft is 1.31m 2 for a total dimension of the tower area (AT) and 408 mm for diameter Total Tower(DT), and 3 mm for the reactor tube wall thickness. In addition, the test results of oilthat has been processed using distillation machine laboratory scale show still makesdiesel specifications in accordance with standards established by the Government,namely the specifications for specific gravity, viscosity, water content, maximumheating and visual appearance.